Resolution of the city of Annapolis, Md. - Brice, James, active 1783.
Resolution (1783 May 12-26) of the city of Annapolis, Md., requesting the Continental Congress to choose Annapolis as the capital of the United States. Signed by James Brice, Mayor.
Mayor of Annapolis, Md.
Collection material in English.
Forms part of: Miscellaneous Manuscripts collection.
Keywords: Mayors -- Maryland -- Annapolis